2022
DOI: 10.3389/fbioe.2021.819651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of miRNA-Modified Exosomes in Animal Models of Spinal Cord Injury: A meta-Analysis

Abstract: Background: Spinal cord injury (SCI) is currently not completely curable. Exosomes have been widely used in preclinical studies of spinal cord injury. Here, in this meta-analysis, we focused on evaluating the overall efficacy of therapies based on miRNA-modified exosomes on functional recovery in animal models of SCI.Methods: PubMed, embase and Web of Science library databases were searched. Relevant literature was included, and the random effects model was used to assess the overall effect of the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In terms of motor function scores on day 28 after SCI, this study found that miRNA-modified EVs therapy was effective in improving motor function scores compared with EVs alone or control therapy, and this is consistent with a recent study by Hu et al ( 2021 ). However, our network meta-analysis also investigated motor function scores on day 3 and day 14 after SCI, whereas the recent meta-analysis only examined motor function scores on day 28.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of motor function scores on day 28 after SCI, this study found that miRNA-modified EVs therapy was effective in improving motor function scores compared with EVs alone or control therapy, and this is consistent with a recent study by Hu et al ( 2021 ). However, our network meta-analysis also investigated motor function scores on day 3 and day 14 after SCI, whereas the recent meta-analysis only examined motor function scores on day 28.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, EVs have gained significant attention as potential therapeutic vehicles for delivering cargo to target cells, which is mainly due to their ability to penetrate the blood–brain barrier (BBB) [ 167 , 168 ] However, so far, research investigating the potential therapeutic value of EVs in spinal cord injury is scarce. One possible use of EVs in the treatment of spinal cord injury is to deliver therapeutic agents, such as growth factors or stem cells, directly to the site of the injury ( Figure 3 B) [ 169 ]. This approach may be able to promote the regeneration of damaged nerves and improve functional recovery.…”
Section: Discussion and Therapeutic Approachesmentioning
confidence: 99%
“…When the measure of variance reported was Standard Error of Mean (SEM), we inverted SEM to Standard Deviation (SD) first. Considering that different species and measurements in animals vary greatly, we used a standardized mean difference (SMD) to standardize the results to a uniform scale [ 21 ].…”
Section: Methodsmentioning
confidence: 99%